IMPROVING STUDENTS’ READING COMPREHENSION THROUGH GUIDED READING STRATEGY - ADELIA HUTAHURUK; EVA NURCHURIFIANI; FEBRIYANTI (JETA (Journal of English Teaching and Applied Linguistic), 2022)
The study was aimed to increase students’ reading comprehension through Guided Reading strategy at the eleventh grade of SMA Negeri 1 Natar 2021/2022. The subjects of research were 35 students. The research was focused to increase students’ learning activities and students’ reading comprehension. The improvement of students’ reading comprehension showed mean score in pre-cycle was 58.71, there were 10 students or 28.57% who achieved target score of Minimum Mastery Criteria. The mean score in cycle 1 was 72.14, there were 20 students who achieved score above Minimum Mastery Criteria or 57.14%. The improvement of pre-cycle to cycle 1 was 13.43 or 28.57%. The mean score of cycle II was 81.82, there were 29 students who achieved score above Minimum Mastery Criteria or 82.85%. The improvement of reading test from cycle 1 to cycle 2 was 9.68 or 25.715%. While, from the students’ learning activities, the improvement of students’ learning activities showed mean score of students’ learning activities in cycle I was 7.26 with the criteria was quite active. While, the mean score of students’ learning activities in cycle II was 7.89 with the criteria was active. It could be concluded Classroom Action Research by conducting Guided Reading strategy improved students’ reading comprehension and students’ learning activities.